Internet feminism: how social networks contribute to the development of the fourth feminist wave in Brazil - Cantú Rodrigues Soares, Amanda (2021)
This article seeks to analyze how social networks contribute to the development of the fourth feminist wave in Brazil. Data such as the increase in the number of searches on online platforms, and the multiplication of feminist content pages on social networks, highlight the growing debate on the subject and justify the study’s relevance. The article reports on the development of the feminist movement, from its emergence to the current insurrection, and how it was formed. To this end, it uses bibliographic studies on feminism and the use of virtual space by social movements as a methodology, and the case study of the Brazilian feminist collective Não Me Kahlo. It also uses an interview with one of its founders and the quantitative analysis of the publications on the collective page on Facebook during January and June 2019. Based on this methodology, the study identifies the direct association between the current feminist insurrection and social networks as tools for communication, organization, and popularization of feminist content. The research also points out the benefits and difficulties that the use of social networks add to the current scenario of feminist activism.